Auctions : Theory and Possible Applications to Economies in Transition - Mehra, Rajnish (IMF Working Papers; Working Paper ;, 1993)
A major effort is taking place in many parts of the world to establish market-oriented institutions, a development that is particularly evident in the context of the transforming economies in Eastern Europe and the republics of the former Soviet Union. Against this background, this paper assesses various auction techniques to price and allocate government securities, refinance credit, foreign exchange, and state assets in the context of privatization programs. Before making our recommendations on the appropriate format for auctioning these items, the paper explains basic auction formats and assesses the advantages and disadvantages of these formats drawing on the existing, and mostly theoretical, literature.